Assessment of mixing quality in full-scale, biogas-mixed anaerobic digestion using CFD. (October 2018) - Dapelo, Davide; Bridgeman, John
Graphical abstract: Highlights: Euler-Lagrange CFD model is applied to industrial gas-mixed anaerobic digester. Mixing criteria in literature are assessed. New qualitative criterion is proposed. Current biogas injection for mixing is generally inefficient. Switching injection between 2 nozzle series every minute greatly improves mixing. Abstract: An Euler-Lagrange CFD model is applied to a full-scale, biogas-mixed anaerobic digester to improve mixing efficiency and improve overall performance. Two quantitative mixing criteria previously adopted in anaerobic digestion (viz., uniformity index and dead volume) are critically assessed for the first time. A novel qualitative method is introduced to clarify the output of the quantitative methods. The first-ever quantitative assessment of mixing quality in full-scale, biogas-mixed anaerobic digestion is then proposed, and a strategy to improve mixing, involving the combined use of concentric nozzle manifolds at the base of the digester, is evaluated.